Formulation and Physical Evaluation of CTM Tablets by Direct Compression Method: A Systematic Literature Review - Astriani Nurjanah; Nurlelah, Neni (Eureka Herba Indonesia, 2023)
The direct compression method is one of the well-known formulation approaches in tablet manufacture. In this method, the active ingredients and additives of the formulation are mixed together and then compressed into tablets using a special device such as a compression machine. This study is a systematic review that aims to explore the formulation and physical evaluation of CTM tablets by direct compression method. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the formulation and physical evaluation of CTM tablets by direct compression method. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The direct compression method enables the manufacture of CTM tablets in a single production step, reducing the complexity and time required. The CTM tablet formulation process using the direct compression method involves homogeneous mixing of the raw materials and direct compression of the mixture into tablets using a compression machine. The direct compression method has advantages in production efficiency, simplicity, and cost-effectiveness, controlling the dosage of the drug contained in the tablet, and physical uniformity of the tablet. However, the direct compression method also has drawbacks, such as the risk of material segregation, difficulty in achieving controlled drug release, and the potential for direct effects on the active ingredients. Physical evaluation of tablets involves measuring the weight, thickness, and diameter of the tablets, as well as hardness or compressive strength tests to ensure the physical quality of the tablets produced. Drug release tests and dissolution tests were carried out to ensure that the CTM tablets released the drug consistently and under control according to regulatory requirements. Stability tests and chemical tests were carried out to check the physical and chemical changes of the tablets during storage and to ensure the integrity and purity of chlorpheniramine.